Immunogenicity and protective efficacy of an inactivated infectious bronchitis virus vaccine candidate from a local isolate of Bangladesh. - Parvin, Mst Kohinoor; Haque, Md Enamul; Haque, Mohammad Aynul; Kamal, Md Mostofa; Sadekuzzaman, Mohammad; Hayat, Sajedul; Rahman, Md Tanvir; Siddique, Mahbubul Pratik; Nahar, Sham Soun; Khasruzzaman, A K M; et al. (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: Infectious bronchitis (IB), a highly infectious acute viral disease, is a major burden to the chicken industry worldwide. The research aimed to develop an inactivated IB vaccine using local isolates and assess its immunogenicity compared to other commercial live IB vaccines. Materials and Methods: An inactivated vaccine using a candidate IB virus (PP067159.1: Alim_IB_1001) of the QX genotype was developed according to WOAH guidelines. Chickens were vaccinated with three doses (0.25, 0.5, and 1.0 ml) at 7 days old, with a booster at 37 days old via subcutaneous (SC) and intramuscular (IM) routes. Blood samples were collected on days 7, 37, and 67 to measure immune response by indirect ELISA. On day 67, chickens were challenged with a virulent IBV strain to assess vaccine protection. The experimental IB vaccine’s immunogenicity, protective efficacy, and antibody duration was compared to a live IB vaccine (Live CEVAC® IBird) using three vaccination schedules: killed-followed-killed, live-followed-killed, and live-followed-live. Results: Chickens vaccinated with SC with 1.0 ml showed higher antibody titers compared to other SC and IM routes of vaccination. SC vaccination with 0.5 and 1 ml provided the highest protection (93%). The killed-followed-killed vaccination method produced a more consistent and protective level of antibody titers in chickens compared to the other vaccination schedules. The experimental inactivated IB vaccine led to a higher survival rate (93%) compared to live-followed-killed (87%) and live-followed-live (73%), with statistical significance (p < 0.01). All three chicken groups maintained protective antibody titers (> 396) at 307 days, but titers declined faster in the live-followed-live and live-followed-killed groups compared to the killed-followed-killed group. Conclusion: The study found that the experimental inactivated IB vaccination can protect commercial-layer chickens from natural IB outbreaks of the QX genotype. J. Adv. Vet. Anim. Res., 11(3): 592–600, September 2024 http://doi.org/10.5455/javar.2024.k809